HOME-BASED SELF-DELIVERED MIRROR THERAPY FOR PHANTOM PAIN: A PILOT STUDY - Darnall, Beth D. (J Rehabil Med, 2012)
OBJECTIVE: To test the feasibility and preliminary efficacy of self-delivered home-based mirror therapy for phantom pain. DESIGN: Uncontrolled prospective treatment outcome pilot study. PARTICIPANTS: Forty community-dwelling adults with unilateral amputation and phantom pain >3 on a 0–10 numeric rating scale enrolled either during a one-time study visit (n = 30) or remotely (n = 10). METHODS: Participants received an explanation of mirror therapy and were asked to self-treat for 25 min daily. Participants completed and posted back sets of outcomes questionnaires at months 1 and 2 post-treatment. Main outcome was mean phantom pain intensity at post-treatment. RESULTS: A significant reduction in mean phantom pain intensity was found at month 1 (n = 31, p = 0.0002) and at month 2 (n = 26, p = 0.002). The overall median percentage reduction at month 2 was 15.4%. Subjects with high education (>16 years) compared with low education (<16 years) (37.5% vs 4.1%) had greater reduction in pain intensity (p = 0.01). CONCLUSION: These findings support the feasibility and efficacy of home-based self-delivered mirror therapy; this low-cost treatment may defray medical costs, therapy visits, and the patient travel burden for people with motivation and a high level of education. More research is needed to determine methods of cost-effective support for people with lower levels of education.